Fabrication of hybrid graphene-polyethersulfone supported liquid membrane for acetic acid removal from oil palm frond biomass hydrolysate - Norlisa, Harruddin (2020)
Conversion of lignocellulosic biomass to biofuel gives a great contribution to the supplement of renewable energy source. To achieve this purpose, acid hydrolysis was used to hydrolyze the lignocellulosic materials to fermentable sugars. Acid hydrolysis is efficient, simple and fast method compared to enzymatic hydrolysis. However, the major problem encountered during the hydrolysis process is the releasing of acetyl group such as acetic acid (AA) as byproducts with the hydrolyzed sugar component. AA can acts as inhibitors to the enzymatic conversion of sugar into the final product of ethanol or other chemicals. Therefore, AA needs to be removed from the biomass hydrolysate to maximize the yield of products. This study focused on development of the hybrid membrane support for used in the supported liquid membrane (SLM) process for AA removal using vapor induced phase separation (VIPS) technique. The hybrid membrane were characterised in term of morphology by scanning electron microspcope (SEM) and field emission scanning electron microscope (FESEM), porosity, membrane hydrophobicity and mechanical strength. The organic liquid membrane phase for extraction of AA was formulated in the first part of the study. The best liquid membrane phase and stripping agent were 0.5 M tri-n-octyl-amine (TOA) carrier in 2-ethyl-1- hexanol diluent and 0.5 M NaOH, respectively. Incorporation of 0.1 wt% graphene in the hybrid polyethersulfone (PES) flat sheet membrane support was found significantly improved the tensile stress of the hybrid membrane from 740 kPa to 1790 kPa, an improvement about 140% in mechanical strength compared to pristine PES membrane. The contact angle of the hybrid membrane also increased from 81.92º to 122.35º and becoming highly hydrophobic membrane support that improved the SLM stability. PES- 0.1graphene (G) membrane support remains stable for more than 116 hours (12 SLM cycles) without requires reimpregnation in the liquid membrane phase compared to the pristine membrane that only stable for 16 hours (2 SLM cycles). The best condition to prepare the flat sheet hybrid membrane through VIPS are using 50 °C coagulation bath temperature, 30 second air exposure time and 80% air humidity. It showed 95% removal of the AA from 10 g/l aqueous solution. During production of hollow fiber membrane support, impregnation time of liquid membrane and feed flow operating modes of PES-0.1G hollow fiber membrane was studied. The best impregnation time for preparing hollow fiber module was 4 hours. The feed phase flowed in lumen side (Mode I) showed better separation performance compared to the shell side (Mode II). The removal percentage of AA using hollow fiber operated with Mode I and Mode II were 80.1% and 42.4%, respectively. The capability of SLM process in removing of AA from oil palm frond (OPF) biomass hydrolysate was tested using PES-0.1 G flat sheet and hollow fiber membrane. The concentration of AA in the OPF hydrolysate was reduced from 6.83 g/l to 1.33 g/l and 2.01 g/l using flat sheet and hollow fiber SLM, respectively. Both SLM systems meet the minimum concentration of AA that should present in the biomass hydrolysate for ensuring highest ethanol production which is less than 5 g/l. Thus, the SLM system using hybrid G-PES membrane support developed in this study is proven effective for removing AA from aqueous solution and OPF biomass hydrolysate.